Drawing a hypothesis : figures of research - Gansterer, Nikolaus (New York : Springer, 2011)
Index of Figures. - Drawing a Hypothesis (Preface), Nikolaus Gansterer. - A Line with Variable Direction, which Traces No Contour, and Delimits No Form, Susanne Leeb. - I Must Be Seeing Things, Clemens Krummel. - Subjective Objectivities, Jorg Piringer. - Grapheus Was Here, Anthony Auerbach. - Asynchronous Connections, Kirsten Matheus. - Distancing the If and Then, Emma Cocker. - Drawing Interest / Recording Vitality, Karin Harrasser. - Nonself Compatibility in Plants, Monika Bakke. - Hypotheses non Fingo or When Symbols Fail, Andreas Schinner, - Wiry Fantasy, Ferdinand Schmatz. - Reading Figures, Helmut Leder. - Collection of Figures of Thoughts, Gerhard Dirmoser. - Radical Cartographies, Philippe Rekacewicz. - 3 Elements, Axel Stockburger. - Dances of Space, Marc Boeckler. - Collection of Emotions and Orientation, Christian Reder. - On the Importance of Scientific Research in Relation to Humanities, Walter Seidl. - Interpersonal Governance Structures, Katja Mayer. - The Afterthought of Drawing: 6 Hypotheses, Jane Tormey. - The Hand, The Creatures, The Singing Garden & The Night Sky, Moira Roth. - The Unthought Known, Felix de Mendelssohn. - Processing the Routes of Thoughts, Kerstin Bartels. - An Attempted Survey, Section.a. - The Line of Thought, Hanneke Grootenboer. - Strong Evidence for Telon-priming Cell Layers in the Mammalian Olfactory Bulb, M. L. Nardo, A. Adam, P. Brandlmayr, B. F. Fisher. - Expected Anomalies Caused by Increased Radiation, Christina Stadlbauer. - On Pluto 86 Winter Lasts 92 Years, Ralo Mayer. -- Appendix: Personalia. Subindex. Index of Names. Colophon. Notices.
boek